The relationship between sensory processing sensitivity and medication sensitivity: brief report - Jagiellowicz, Jadzia; Acevedo, Bianca P.; Tillmann, Teresa; Aron, Arthur; Aron, Elaine N. (Frontiers in Psychology, 2024)
Sensory processing sensitivity (SPS) is a biological/temperament trait that is associated with greater awareness of and reactivity to the environment, which results in amplified responses to various stimuli, and possibly medications. We investigated the relationship between SPS and medication sensitivity in three studies. Participants (ages 18–81) were recruited from university (Study 1: N = 125; Study 2: N = 214) and online (Study 3: N = 351) samples. In each study, participants completed a medication sensitivity scale, the standard highly sensitive person (HSP) scale to assess SPS, and a negative affectivity (NA) scale as a control variable. All three studies found moderate, significant correlations between SPS and medication sensitivity (r = 0.34, p < 0.001: r = 0.21, p = 0.003; r = 0.36, p < 0.001, respectively). Correlations remained significant, and similar, when controlling for NA and gender; and there were no significant interactions with gender. In sum, our results suggest that SPS is associated with medication sensitivity, even when considering NA and gender. Thus, future work might consider SPS when investigating recommended medication, medication dosage, effectiveness, and adverse drug reactions.